STOCHASTIC MODEL OF CHANGING INTERPRODUCTION FLOWS - Gerasin, S. N.; Kozlov, M. A. (Radio Electronics, Computer Science, Control, 2024)
Stochastic interpretation of model of dynamic allocation of resources is offered. Model formalism is utilized by the language of inhomogeneous Markov’s chains. Possibility of the use of th offered model is solution in the tasks of economic prognostication.